Skin Collagen and Thickness in Women with Hirsuties. Issue 5738 (26th December 1970) - Shuster, Sam; Black, Martin M.; Bottoms, Eva
Abstract : Total skin collagen is greatly increased in women with hirsuties. This is presumably due to androgen, whether locally produced or circulating.